2012
DOI: 10.1002/qua.24194
|View full text |Cite
|
Sign up to set email alerts
|

Density functional study on the geometric features and growing pattern of BnPm clusters with n = 1–4, m = 1–4, n + m ≤ 5

Abstract: The bonding features of BnPm clusters (n = 1–4, m = 1–4, n + m ≤ 5) are studied within the framework of the density functional theory following a systematic growing mechanism. Some stable geometries are found to agree well with results reported previously in the literature. Other geometries are found to be more stable than structures reported elsewhere for small B/P aggregates. To the best of our knowledge, stable geometries for BP4 are reported for the first time. It is found that small B/P clusters with up t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
1
0
0
Order By: Relevance
“…Interestingly, we observed that increasing the spin multiplicity of clusters to 4, 5, and 6 do not affect final structure of the clusters; however, clusters with higher spin multiplicity are very unstable energetically (in some cases more than 2 eV). Results of Table 1 show that the dipole moment of Al clusters strongly depend on the size and structural symmetry of the clusters which is in agreement with the results of references [2,28,29]. It has been reported that clusters with odd number of atoms are less symmetric and have larger values of dipole moment while clusters with even number of atoms are more symmetric and have smaller values of dipole moment [2].…”
Section: Resultssupporting
confidence: 88%
“…Interestingly, we observed that increasing the spin multiplicity of clusters to 4, 5, and 6 do not affect final structure of the clusters; however, clusters with higher spin multiplicity are very unstable energetically (in some cases more than 2 eV). Results of Table 1 show that the dipole moment of Al clusters strongly depend on the size and structural symmetry of the clusters which is in agreement with the results of references [2,28,29]. It has been reported that clusters with odd number of atoms are less symmetric and have larger values of dipole moment while clusters with even number of atoms are more symmetric and have smaller values of dipole moment [2].…”
Section: Resultssupporting
confidence: 88%